2017
DOI: 10.1002/cbin.10754
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‐216b inhibits cell proliferation and migration in human melanoma by targeting FOXM1 in vitro and in vivo

Abstract: MicroRNAs (miRNAs) play an increasingly important role in cancer growth by coordinately suppressing genes that control cell migration, proliferation, and invasion. The above results can be achieved through the regulation of gene expression by miRNAs by suppressing translation or the direct sequence-specific degradation of the targeted mRNA. In the present study, we indicate that the expression of miR-216b could be effectively repressed both in human melanoma tissues through a comparison with primary melanoma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 25 publications
(30 reference statements)
1
12
0
Order By: Relevance
“…In this same study, the authors identify forkhead box protein M1 (FOXM1) as a direct target, and ectopic expression of miR-216b led to a decrease in FOXM1 protein levels and percentage of Ki-67-positive cells in xenograft models. A similar mechanism has been shown for melanoma (99), hepatocellular carcinoma (100), non-small-cell lung carcinoma (101), and osteosarcoma (102), and low miR-216b levels in tumors are independent poor prognostic indicators in many of these cancers. In pancreatic cancer, this miRNA functions in a tumor-suppressive way by targeting translationally controlled tumor protein (TPT1), and levels of this miRNA are significantly associated with large tumor size and advanced TNM stage (103).…”
Section: Mir-494: Upregulated In Hypoxia In Canine High-grade Glioma supporting
confidence: 62%
“…In this same study, the authors identify forkhead box protein M1 (FOXM1) as a direct target, and ectopic expression of miR-216b led to a decrease in FOXM1 protein levels and percentage of Ki-67-positive cells in xenograft models. A similar mechanism has been shown for melanoma (99), hepatocellular carcinoma (100), non-small-cell lung carcinoma (101), and osteosarcoma (102), and low miR-216b levels in tumors are independent poor prognostic indicators in many of these cancers. In pancreatic cancer, this miRNA functions in a tumor-suppressive way by targeting translationally controlled tumor protein (TPT1), and levels of this miRNA are significantly associated with large tumor size and advanced TNM stage (103).…”
Section: Mir-494: Upregulated In Hypoxia In Canine High-grade Glioma supporting
confidence: 62%
“…16 The cells in the 24-well culture plates were transfected with FoxM1-WT or FoxM1-MUT and miR-216b mimics (20 nmol/L) by Lipofectamine™ 2000. The MUT sequence of FoxM1 has been confirmed in a previous study.…”
Section: Luciferase Assaymentioning
confidence: 99%
“…Numerous studies have indicated that miRNAs play pivotal roles in several biological processes, including cell proliferation, cycle, apoptosis, differentiation, migration and metastasis (13)(14)(15). Recently, dysregulation of miRNA expression has been observed in various types of human cancers, such as melanoma (16), gastric (17), lung (18) and colorectal cancer (19) and glioma (20). In the context of cancer, miRNAs may serve as oncogenes or tumour suppressors in tumourigenesis and tumour development by negatively regulating tumour suppressors or oncogenes (21,22).…”
Section: Introductionmentioning
confidence: 99%